Community-Based Hypertension Screening and Mindfulness Intervention in Awu Village, Banggai Regency - Nurarifah; Tampuyak, Irawati (Jurnal Pengabdian Masyarakat Lentora, 2025)
Background: Hypertension is a major modifiable risk factor for cardiovascular disease. Community-based programs that combine screening, education, and practical self-management skills are crucial for its prevention and control. Objective: This community service initiative aimed to implement and evaluate such a program in Awu Village. Methods:  The program consisted of three integrated components: (1) blood pressure screening for all participants, (2) educational sessions on non-communicable diseases and hypertension, assessed by pre- and post-tests, and (3) a practical mindfulness training session introducing techniques for stress management. Results: Screening of 45 participants revealed a high prevalence of pre-hypertension (42.2%), indicating a significant risk for progression to clinical hypertension. The educational intervention successfully improved knowledge, with the proportion of participants in the "good" knowledge category increasing from 53% to 76%. During mindfulness practice, participants were observed to be focused and relaxed, successfully engaging with the techniques. Qualitative feedback indicated that participants found the session beneficial for stress relief. Conclusion and Suggestion: This integrated program was effective in identifying cardiovascular risk, improving health literacy, and introducing a practical self-management tool. The high pre-hypertension rate underscores the urgency of such interventions. For sustained impact, it is recommended that the local health post (Posbindu) incorporate brief mindfulness exercises into its regular activities and establish community support groups to foster long-term practice, thereby contributing to the primary prevention of hypertension in Awu Village.